2013
DOI: 10.1136/bmjopen-2012-002072
|View full text |Cite
|
Sign up to set email alerts
|

The Sydney Multisite Intervention of LaughterBosses and ElderClowns (SMILE) study: cluster randomised trial of humour therapy in nursing homes

Abstract: ObjectivesTo determine whether humour therapy reduces depression (primary outcome), agitation and behavioural disturbances and improves social engagement and quality-of-life in nursing home residents.DesignThe Sydney Multisite Intervention of LaughterBosses and ElderClowns study was a single-blind cluster randomised controlled trial of humour therapy.Setting35 Sydney nursing homes.ParticipantsAll eligible residents within geographically defined areas within each nursing home were invited to participate.Interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 33 publications
1
83
2
2
Order By: Relevance
“…For example, recent pragmatic trials of support programmes (Kurz et al, 2012;Low et al, 2013;Van de Ven et al, 2013;Waldorff et al, 2012), telecare (Bardsley, Steventon, & Doll, 2013), training interventions (Beer et al, 2011;Spijker et al, 2011) and system enhancements or novel methods of delivering services (Goldberg et al, 2013;Meeuwsen et al, 2012;Nourhashemi et al, 2010;Van Houdt & De Lepeleire, 2010) all report no positive effects compared with the control 'usual care' condition. One study nonetheless demonstrated improvements in the patient experience and family carer satisfaction (Goldberg et al, 2013) whilst others point to problems with delivery of the intervention by practitioners such as poor adherence and variation in practice (Low et al, 2013;Spijker et al, 2013;Wenborn et al, 2013). Thus, failure to report positive outcomes may reflect genuine ineffectiveness where the intervention has failed to address basic human values such as dignity and autonomy (Vernooij-Dassen, Leatherman, & Rikkert, 2011) or may be a consequence of practical difficulties in conducting applied research in routine care settings (Iliffe et al, 2008).…”
Section: Success and Failure Of Psychosocial Interventionsmentioning
confidence: 99%
“…For example, recent pragmatic trials of support programmes (Kurz et al, 2012;Low et al, 2013;Van de Ven et al, 2013;Waldorff et al, 2012), telecare (Bardsley, Steventon, & Doll, 2013), training interventions (Beer et al, 2011;Spijker et al, 2011) and system enhancements or novel methods of delivering services (Goldberg et al, 2013;Meeuwsen et al, 2012;Nourhashemi et al, 2010;Van Houdt & De Lepeleire, 2010) all report no positive effects compared with the control 'usual care' condition. One study nonetheless demonstrated improvements in the patient experience and family carer satisfaction (Goldberg et al, 2013) whilst others point to problems with delivery of the intervention by practitioners such as poor adherence and variation in practice (Low et al, 2013;Spijker et al, 2013;Wenborn et al, 2013). Thus, failure to report positive outcomes may reflect genuine ineffectiveness where the intervention has failed to address basic human values such as dignity and autonomy (Vernooij-Dassen, Leatherman, & Rikkert, 2011) or may be a consequence of practical difficulties in conducting applied research in routine care settings (Iliffe et al, 2008).…”
Section: Success and Failure Of Psychosocial Interventionsmentioning
confidence: 99%
“…parents), other times other individuals are being involved by the clowns (e.g. other patients) or are working together with the clowns (e.g., hospital staff; see also Dionigi et al, 2012;Low et al, 2013 Algoe and Haidt (2009) subsume the emotions of elevation, gratitude and admiration under other-praising emotions, which were elicited explicitly in observers who witnessed an act of moral virtue or beauty such as charity or generosity, and differed in physiological experiences and action tendencies from emotions elicited when watching funny films (e.g., amusement). Given that a clown doing beneficial work in a hospital can be viewed as an act of moral beauty, it could be argued that observers experience different emotions than participants of clown interventions.…”
Section: Possible Roles During a Hospital Clown Interventionmentioning
confidence: 99%
“…Linge (2013) concludes that hospital clowns apply a mixed method of humor and empathy and thereby elicit surprise, joy, acknowledgement, appreciation, and a close connection to the clown (magical attachment) in children and adolescents. The third source (quantitative studies using an experimental design) compares clown-induced changes such as unspecific positive affect (feeling happy) and the reduction of worries (e.g., Costa Fernandes & Arriaga, 2010), agitation (Low et al, 2013), or changes in physical conditions such as electrodermal activity, and blood volume pulse (Kingsnorth, Blain, & Keever, 2010) to control groups without intervention. However, nothing much can be said about the effects on positive emotions.…”
Section: Settingmentioning
confidence: 99%
“…Vaillant (e.g., 2000) has argued that humor may contribute to healthy aging (as a mature defense mechanism). There are also humor-based programs in the elderly that are effective in ameliorating depression, anxiety, or pain (e.g., Ganz & Jacobs, 2014;Hirsch, Junglas, Konradt, & Jonitz, 2010;Konradt, Hirsch, Jonitz, & Junglas, 2013;Low et al, 2013; for an overview see Ruch & McGhee, 2014), or in enhancing positive affect in habitants of residential homes (Houston, McKee, Carroll, & Marsh, 1998). Humor is also potent in inducing the positive emotion of amusement (Ruch, 2001(Ruch, , 2009, which may be helpful in the building of resources for well-being (Fredrickson, 1998).…”
Section: Introductionmentioning
confidence: 99%